Improving Tenaga Nasional Berhad (TNB)’s efficiency through Business Process Reengineering (BPR) / Noorasita Ismail ... [et al.] - Ismail, Noorasita; Rostam Afandi, Erza Syahanas; Md. Yusoff, Noorazlina (2018)
The purposes of the study are to identify and analyse the causes of inefficient supply application process and non-compliance to Performance Standard of Electricity Supply Services of TNB as regulated by EC at TNB Penang. The study also strives to provide general evaluation of utilization of Information Technology in supply application process at TNB Penang. Lastly, the study aims to propose suitable strategies of Business Process Reengineering (BPR) that could be taken by TNB Penang to improve the efficiency of the supply application process and compliance towards Performance Standard of Electricity Supply Services of TNB as regulated by EC. Business analysis tools comprised of Root Cause Failure Analysis (RFCA) which is divided into Cause and Effect Diagram (CED) and Tree Diagram are utilized to identify and analyse the causes of inefficient supply application process and non-compliance and in the same time conduct general evaluation of utilization of Information Technology in supply application process at TNB Penang. Pareto Analysis and Generic Model of BPR are adopted to develop suitable strategies of Business Process Reengineering (BPR). Based on the analysis conducted, three causes identified are supply application process, employees’ competencies and Information Technology (IT). Strategies recommended are comprised of reengineering the current supply application process, proposed specific types of training for employees involve in supply application process and develop mentor-mentee program in the organization to resolve the issue related to employees competencies. The last recommendation is the aggressive utilization of IT to rapidly improve the inefficiency identified in the supply application process at TNB Penang.